A percepção de saúde de homens e mulheres: uma análise para as áreas rurais do Nordeste e Sul do Brasil - Malacoski, Fernanda Cristina Ferro (2019)
Health is a concept that has been incorporated into economic analysis because it transcends biological issues and covers all spheres of life of the individual and the society in which it is inserted. The various dimensions, such as type of employment, income, schooling, age and sex, are important factors in explaining the individual's state of health. This is because, studies show that the socioeconomic conditions interfere in the result of the subjective evaluation of the state of health that the individual makes of itself. Health allows the individual to invest more in himself and has a higher level of well-being; be more productive; earn more income, and also have more years available for work. All of these factors contribute to the economy, development, poverty reduction and enhancement of the nation's well-being. The main objective of the present study was to analyze the perception of the health status of men and women living in rural areas of the South and Northeast of Brazil, based on data from the PNS (2013) - which provides information on the subjective health assessment for all Brazil. The choice of these regions is justified by the socioeconomic contrasts that affect the perception of health status. It is added that a regional analysis on the subject is still little explored in Brazil. The methodology had a descriptive analysis, as well as the application of Logit and Logit ordinal models, to elucidate the effect of socioeconomic characteristics on the result of the perception of health status of the population studied. The main results pointed to the importance of the variables age, white color, head of household, income, agricultural occupation, number of medical appointments, have been diagnosed with any disease and have health insurance. Thus, in addition to the variables that are directly related to the individual's biological health, other socioeconomic variables were significant. Finally, the estimated results are in accordance with the theoretical production on the subject. In both estimates the signs and variables were similar, indicating that there is consistency in the variables used in this study. Still, education and income, widely discussed in the literature as related to health self-assessment, were not significant as expected.